The Potentially Positive Role of PRPs in Preventing Femoral Tunnel Widening in ACL Reconstruction Surgery Using Hamstrings: A Clinical Study in 51 Patients. (6th November 2014) - Starantzis, Konstantinos A.; Mastrokalos, Dimitrios; Koulalis, Dimitrios; Papakonstantinou, Olympia; Soucacos, Panayiotis N.; Papagelopoulos, Panayiotis J.
Abstract : Purpose . In this study, the early and midterm clinical and radiological results of the anterior cruciate ligament (ACL) reconstruction surgery with or without the use of platelet rich plasma (PRP) focusing on the tunnel-widening phenomenon are evaluated. Methods . This is a double blind, prospective randomized study. 51 patients have completed the assigned protocol. Recruited individuals were divided into two groups: a group with and a group without the use of PRPs. Patients were assessed on the basis of MRI scans, which were performed early postoperatively and repeated at least one-year postoperatively. The diameter was measured at the entrance, at the bottom, and at the mid distance of the femoral tunnel. Results . Our study confirmed the existence of tunnel widening as a phenomenon. The morphology of the dilated tunnels was conical in both groups. There was a statistical significant difference in the mid distance of the tunnels between the two groups. This finding may support the role of a biologic response secondary to mechanical triggers. Conclusions . The use of RPRs in ACL reconstruction surgery remains a safe option that could potentially eliminate the biologic triggers of tunnel enlargement. The role of mechanical factors, however, remains important.